2021
DOI: 10.1177/00332941211043453
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Work Value and Ethical Practices Amongst Primary School Teachers, Demographics, Intervention, and Impact

Abstract: The rate of value decadence and degeneration of moral value as it applies to work ethic amongst teachers is worrisome, especially in Nigeria. This value decadence amongst Nigerian teachers could have been triggered off as a result of their false perceptions in placing demands. This study therefore investigated the effect of rational emotive occupational intervention on the perceptions of work value and ethical practices amongst teachers in primary schools in Nigeria. Randomized group control intervention was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…As the present study showed that group and gender interaction effects had a substantial impact on the occupational stress levels of technical college teachers, this is not in line with past study that found that there is no interaction effect of rational emotive occupational health coaching and gender. [ 29 ] The variation could be due to the work engagement by the teachers. Unlike the present study, [ 29 ] the reviewed study sampled primary school teachers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the present study showed that group and gender interaction effects had a substantial impact on the occupational stress levels of technical college teachers, this is not in line with past study that found that there is no interaction effect of rational emotive occupational health coaching and gender. [ 29 ] The variation could be due to the work engagement by the teachers. Unlike the present study, [ 29 ] the reviewed study sampled primary school teachers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] The variation could be due to the work engagement by the teachers. Unlike the present study, [ 29 ] the reviewed study sampled primary school teachers. Possibly, the exposure and risks involved in the 2 work environments may not be the same, in that, the role expectation of male and female teachers in the 2 levels (primary schools and technical college) of education differs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People believe that irrational thoughts about an event influence emotions and behaviour rather than the event itself (Ellis, 1977 ). This is why Rational Emotive intervention will be used in this study since it has been used by many researchers (Ede et al, 2019 , 2020 ; Ede, Okeke, Adene & Areji, 2021 ; Ede, Okeke & Chinweuba et al, 2021 ; Ede, Okeke & Chukwu, 2021 ; Ede, Okeke, Igbo et al, 2021 ; Ezegbe et al, 2019 ; Ogbuanya et al, 2019 ), however with a different focus. These researchers have concluded that it is effective as a preventive and curative method of psychotherapy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Evidence from the empirical findings has shown that ethics as a concept plays a significant role in individuals’ beliefs which more often than non-affect their emotions and attitudes in evaluating human behavior. [4,5] The statement indicates that ethical principles, including those acceptable norms, are obviously established to maintain limit, control staff measures, and maintain a work environment friendly and good human relationship between the professional and clients to achieve optimum goals. Thus, work ethics indeed could be conceived as both social and professional standard which guides the employee attitudes and conduct in an organization.…”
Section: Introductionmentioning
confidence: 99%